Size Distribution and Growth of young Payangka Fish, Ophieleotris aporos (Bleeker) from Lake Tondano - Mayangsari Kimberli Susanto; Nego E. Bataragoa; Ruddy D Moningkey (Sam Ratulangi University, 2017)
The research was conducted at the location of Lake Tondano, Minahasa District.The young payangka fish, locally known as nike fish by fishermen of the area. This study aims to determine the size distribution, length-weight relationships and to know the captivity growth in the aquarium. The research is expected to be a source of information about the fish of young payangka (Nike) and be able to contribute on the efforts of nike fish management in Lake Tondano for the future. Sampling is done by using a triangular shaped trap (sibusibu) with a length of 4m, width of 1.30m (top), and a mesh size of 0.5mm. The length frequency distribution with the size mode appeared most during the first of observation was in the range of 13.5 to 15.4 class size and changed in size in the third week of the 19.5-21.4 class sizes. Later in the fifth week the mode is in the range of 15.5-17.4 class size and changes in size in the seventh week at the range of 23.5-25.4 class size. The length-weight relationship of the study was showed by allometric growth (b = 2.70; b <3) which means the length increases faster than weight gain. Absolute weight growth of 0.2532g was recorded and absolute length growth of 10.12mm for 12 weeks was observed as well. Growth of a relatively large weight gained with value of 0.067mg occurs between the seventh week and the eighth week.Keywords : Nike Fish, growth, Tondano ABSTRAKPenelitian ini dilaksanakan di lokasi Danau Tondano Kabupaten Minahasa. Ikan payangka muda dikenal dengan sebutan ikan nike oleh masyarakat lokal. Penelitian ini bertujuan untuk mengetahui distribusi ukuran, hubungan panjang-berat dan untuk mengetahui pertumbuhan yang di pelihara di akuarium. Manfaat penelitian yaitu diharapkan dari penelitian ini dapat menjadi sumber informasi mengenai ikan payangka serta payangka muda (Nike) dan mampu memberikan kontribusi bagi upaya pengelolaan ikan nike di Danau Tondano di masa yang akan datang. Pengambilan sampel dilakukan dengan menggunakan alat tangkap serok (sibusibu) yang berbentuk segitiga dan memiliki ukuran panjang 4m, lebar 1,30m (bagian atas), dan ukuran mata jaring 0,5mm. Distribusi frekuensi ukuran panjang dengan modus atau ukuran yang paling banyak muncul pada minggu pertama terdapat pada kelas ukuran 13,5-15,4 dan mengalami perubahan ukuran pada minggu ketiga pada kelas ukuran 19,5-21,4. Selanjutnya pada minggu kelima modusnya ada pada kelas ukuran 15,5-17,4 dan mengalami perubahan ukuran pada minggu ketujuh di kelas ukuran 23,5-25,4. Hubungan panjang dan berat dari penelitian didapatkan hasil pertumbuhan alometrik (b=2,70), b<3 yang artinya pertambahan panjang lebih cepat dari pertambahan berat. Pertumbuhan berat mutlak sebesar 0,2532g dan pertumbuhan panjang mutlak sebesar 10,12mm selama 12 minggu. Pertumbuhan berat yang relative besar nilainya yaitu 0.067mg terjadi antara minggu ketujuh dengan minggu kedelapan.Kata kunci : Ikan Nike, Pertumbuhan, Tondano